ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DAN KOTADI PROVINSI JAWA TENGAH TAHUN ANGGARAN 2019-2023 - Winny Aditya Dewi Suratno; Sri Isnowati (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the influence of the effectiveness ratio of Local Own-Source Revenue (PAD), efficiency, fiscal independence, and PAD growth on the financial performance of regency and city governments in Central Java Province during the 2019–2023 fiscal years. A quantitative approach was employed using purposive sampling across 35 local governments. Secondary data were obtained from Budget Realization Reports (LRA) and analyzed using financial ratio analysis and panel data regression, including Chow Test, Hausman Test, and Lagrange Multiplier Test, as well as multiple linear regression with t-test, F-test, and coefficient of determination (R²). The results indicate that PAD effectiveness and efficiency are in good categories, while fiscal independence remains low, following an instructive pattern. The PAD growth ratio showed a positive trend over the study period. The Random Effect Model was selected as the most appropriate model, with all four ratios having a significant impact—both partially and simultaneously—on financial performance. These findings highlight the importance of strengthening PAD management to enhance fiscal capacity, improve public service delivery, and foster regional competitiveness in a sustainable manner.